GAMBARAN PENGETAHUAN PASIEN TENTANG PERAWATAN GIGI M3 IMPAKSI DI KLINIK CASADIENTA KOTA CIMAHI (Jurnal Terapi Gigi dan Mulut, 2022)
A person's knowledge about the behavior of maintaining dental and oral health is often inconsistent. The current high rate of dental and oral disease is influenced by several factors, one of which is the behavior of people who do not realize the importance of maintaining oral health. Dental health problems that usually appear at the age of 17-25 years, one of which is the growth of the third molars, often the eruption process of the third molars is impacted. Patients aged 17-25 years must have knowledge about impacted third molars so that patients know the appropriate treatment for impacted M3 teeth according to their complaints. The aim of the study was to describe the patient's knowledge about M3 impaski dental care at the Casadienta clinic, Cimahi city. The method used is descriptive research. The population in this study were patients who came to the Casadienta clinic in Cimahi city in Mulan March-April 2022 with an accidental sampling technique of 31 respondents. The data is processed and presented in a frequency distribution table. The results of this study showed that the number of patients who had complaints of impacted teeth was 54.8%, respondents who had a low level of knowledge about impacted M3 teeth were 30%, respondents who had sufficient knowledge about treatment of impacted M3 teeth were 45.2%. The conclusion of this study showed that most of the respondents had complaints of impacted teeth and the level of knowledge of respondents about impacted M3 teeth and their treatment did not yet have a good knowledge category.